The Use of Dialogue-Games toward English-Speaking Ability of German Language Students - Nugroho, Ade; Salija, Kisman; Nur, Sahril; Abdullah, Abdullah; Aeni, Nur (Har Press Indonesia, 2023)
The objectives of this research were to find out whether or not the use of dialogue-games effective for English-speaking ability of German Language Students and to find out whether or not the use of dialogue-games enhances the interest of English-speaking ability of German Language Students. The research conducted a Pre-Experimental design (One Group Pretest - Posttest Study) with only one group (experimental group). The group consisted of 20 students, where the sample was taken by using random sampling technique. The data obtained through the test were analysed by using inferential statistics through IBM SPSS 25.0 version. In conducting the research, the researcher applied dialogue-games to see its effectiveness for students’ English-speaking skill which covered the three components of speaking when the students did the test. They were accuracy, fluency and comprehensibility. Besides, the researcher used questionnaire to see the students’ interest of their English-speaking ability. The research result showed that there was an increase on the students’ English-speaking ability between pre-test and post-test in experimental group after the treatment. Then, it is concluded that dialogue-games were able to give higher contribution to the speaking skill. It was proven by the result of inferential statistics in testing the students’ score either in pre-test and post-test. Based on the result of the data analysis there was a difference between the result of pre-test and post-tes of experimental group, where the mean score of post-tests of experimental group was 6.22 which was higher than the mean score of pre-tests that in only 2.92. The final score of t-test value in speaking skill was higher than the t-table value (6.750 > 1.991). In other words, Hᵢ was accepted and Hₒ was rejected. Furthermore, the data that were collected from the questionnaire showed that the students were interested in English-speaking ability from the treatment in scale of 82 mean score which was categorized as interested.